Th2 polarization of the immune response of BALB/c mice to Ixodes ricinus instars, importance of several antigens in activation of specific Th2 subpopulations - Mejri, Naceur; Franscini, Nicola; Rutti, Bernard; Brossard, Michel (My University, 2001)
BALB/c mice were infested with Ixodes ricinus larvae, nymphs or adults. Expression of IL-4 and IFN-γ mRNA in axillary and brachial draining lymph node cells were measured by competitive quantitative reverse transcription-polymerase chain reaction 9 days after the beginning of primary-infestation. IL-4 mRNA was always higher than that of IFN-γ mRNA for all tick instars. Moreover, IL-4 mRNA expression progressively increased during nymphal primary-infestation with a high burst of expression 7 days after the beginning of infestation. No evolution of IFN-γ mRNA expression was detected. Draining lymph node cells of infested BALB/c produced higher level of IL-4 than IFN-γ following in vitro restimulation with adult tick saliva, salivary gland extract (SGE) or with five selected different chromatographic fractions of SGE. Anti-tick IgG1 antibodies but no IgG2a were detected in BALB/c pluri-infested with I. ricinus nymphs, which confirmed the Th2 polarization of the immune response.
Keywords: Ixodes ricinus; tick instars; BALB; c; antigens; saliva; cytokines; IL-4; IFN-γ; Th2